Non-Hermitian topological phases in an extended Kitaev model. (May 2020) - Maiellaro, A; Citro, R
Abstract: In this work we address the study of topological phase protection of open quantum systems. Using the self-energy formalism, we investigate the paradigmatic case of an extended Kitaev model. The results show how the topological order can be affected by coupling the system to two external leads, giving rise to Non-Hermitian topological phases. Our results could be useful in spectroscopic measurements made on nanowire-based mesoscopic devices.